Predictors of interest in taking pre‐exposure prophylaxis among men who have sex with men who used a rapid HIV‐testing site in Montreal (Actuel sur Rue). Issue 2 (14th July 2015) - Lebouché, B; Engler, K; Machouf, N; Lessard, D; Thomas, R
Abstract : Objectives: The effective use of pre‐exposure prophylaxis (PrEP) as an HIV prevention strategy depends on its uptake by individuals at high risk of infection. Few Canadian data are available on interest in PrEP among men who have sex with men (MSM). This study aimed to identify predictors of interest in PrEP among MSM clients of a rapid HIV‐testing site in Montreal's gay village (Actuel sur Rue). Methods: Data were collected using a self‐administered and a community agent‐administered questionnaire. Among men reporting at least one male sexual partner and visiting the site between July 2012 and November 2013, we aimed to identify sociodemographic, sexual and temporal predictors of interest in taking effective PrEP with logistic regression analyses (univariate and multivariable). Results: Over half (55%; n  = 653) of the sample of 1179 MSM were interested in PrEP. Among the 14 variables considered in the univariate analyses, only (younger) age, (greater) number of sexual partners (in the past 3 months), being part of a serodiscordant couple (in the past 12 months), ever combining sex with drugs and temporal events were associated with interest in PrEP at P  < 0.20 and were included in the multivariable analyses. In the multivariable model, only being part of a serodiscordant couple [adjusted odds ratio (aOR) 2.56; 95% confidence interval (CI) 1.44–4.58], having > 10 partners (aOR 1.73; 95% CI 1.17–2.55) and responding after the publication of Quebec's interim PrEP guidelines (aOR 1.82; 95% CI 1.22–2.71) proved significant. Conclusions: In this assessment of predictors of PrEP interest among Canadian MSM, partnering issues and the arrival of PrEP guidelines in Quebec (10 July 2013) were most closely linked to PrEP interest.